A comparison of high throughput core–shell 2D electrospinning and 3D centrifugal spinning techniques to produce platelet lyophilisate-loaded fibrous scaffolds and their effects on skin cells. Issue 85 (22nd November 2017) - Vocetkova, K.; Buzgo, M.; Sovkova, V.; Rampichova, M.; Staffa, A.; Filova, E.; Lukasova, V.; Doupnik, M.; Fiori, F.; Amler, E.
Abstract : Nanofibres enriched with bioactive molecules, as actively acting scaffolds, play an important role in tissue engineering. Abstract : Among the main aims of tissue engineering certainly belong actively acting scaffolds with a controlled release of bioactive molecules. This is important for cell-free scaffolds in regenerative medicine. The scaffold topology is crucial for cell–scaffold interactions and plays a pivotal role in stimulation of cell adhesion and proliferation through affecting cell morphology and intercellular contacts. The aim of this study was to characterise proliferation of different skin cells on core–shell 2D and 3D nano- and microfibre scaffolds from poly-ε-caprolactone loaded with lyophilised platelets. The electrospinning technique forms dense fibrous 2D scaffolds with limited cell infiltration, whereas the centrifugal spinning enables deep cell penetration due to its open 3D structure. The core of the prepared fibres was loaded with lyophilised platelet fraction and its release was controlled by the Pluronic F-68 concentration. This resulted in the preparation of functionalized scaffolds with a tuneable sustained release lasting more than 30 days. Two dermal cell lines, keratinocytes and fibroblasts, were grown on these functionalized scaffolds. While keratinocytes, epithelial cells, proliferated significantly better on the 2D structure with optimal stimulation of cell proliferation on the scaffolds containing 5% PF-68, fibroblasts proliferated well both on the 2D and 3D scaffolds but with a higher initial adhesion on the 3D forcespun fibre scaffold. Furthermore, a dose-dependent stimulation of proliferation by the released platelet lyophilisate was shown. We have concluded that beside the scaffold composition and its functionalization with bioactive molecules, the scaffold structure plays a significant role in regenerative medicine and dermal tissue engineering.